Pengaruh Variabel Kesesuaian Merk dan Sikap Konsumen pada Sebuah Merk Individu terhadap Sikap Konsumen pada Merk Hasil Aliansi - Singgih Santoso (Fakultas Bisnis UKDW, 2009)
Brand alliances is a popular phenomenom in today's marketing activities. Although that concept has grown in popularity, there has been a little research model that explains the conffict of these alliances on consumer attitudes toward the alliances itself. This research tested relationship between three alliances variables with consumer attitudes toward brand alliances. With between subject experimental design, and the product alliances is between notebook and processor, the result of the research confirmed that attitude toward individual brand before alliances and brand it influenced consumer attitudes toward brand alliances significantly.Keywords : Brand, marketing, customer, attitude.